Andrographis paniculata and Its Main Bioactive Ingredient Andrographolide Decrease Alcohol Drinking and Seeking in Rats Through Activation of Nuclear PPARγ Pathway. (6th January 2021) - Stopponi, Serena; Fotio, Yannick; Cifani, Carlo; Li, Hongwu; Haass-Koffler, Carolina L; Cannella, Nazzareno; Demopulos, Gregory; Gaitanaris, George; Ciccocioppo, Roberto
Abstract: Background and aims: Andrographis paniculata is an annual herbaceous plant which belongs to the Acanthaceae family . Extracts from this plant have shown hepatoprotective, anti-inflammatory and antidiabetic properties, at least in part, through activation of the nuclear receptor Peroxisome Proliferator-Activated Receptor-gamma (PPAR γ). Recent evidence has demonstrated that activation of PPARγ reduces alcohol drinking and seeking in Marchigian Sardinian (msP) alcohol-preferring rats. Methods: The present study evaluated whether A. paniculata reduces alcohol drinking and relapse in msP rats by activating PPARγ. Results: Oral administration of an A. paniculata dried extract (0, 15, 150 mg/kg) lowered voluntary alcohol consumption in a dose-dependent manner and achieved 65% reduction at the dose of 450 mg/kg. Water and food consumption were not affected by the treatment. Administration of Andrographolide (5 and 10 mg/kg), the main active component of A. paniculata, also reduced alcohol drinking. This effect was suppressed by the selective PPARγ antagonist GW9662. Subsequently, we showed that oral administration of A. paniculata (0, 150, 450 mg/kg) prevented yohimbine- but not cues-induced reinstatement of alcohol seeking. Conclusions: Results point to A. paniculata -mediated PPARγactivation as a possible therapeutic strategy to treat alcohol use disorder.